Measurement of Donnan potentials in gels by in situ microelectrode voltammetry - Davis, T. A. (2013)
This work describes the electrochemical methodology for the determination of the Donnan potential from diffusion-limited steady-state voltammograms of acrylamide gels. The technique is based upon the measurement of gel–sol systems that have reached Donnan equilibrium and contain Cd2+ as a probe ion. Au-amalgam microelectrodes are used to measure the Cd concentration in the gel phase relative to the solution phase, thus permitting comparison of the Cd voltammograms obtained in both phases. This approach yields two independent measures of the Donnan potential resulting from (i) the potential shift relative to the reference electrode, and (ii) the enhancement of the Cd2+ wave. Two suites of acrylamide gels containing 0.2% and 0.5% Na-acrylate were studied as a function of ionic strength by varying [NaNO3] and maintaining a constant concentration of the electroactive probe ion, [Cd2+] = 1 · 10 5 mol/L in the equilibrating solutions. Independent model predictions of the Donnan potential as a function of ionic strength that consider the effects of differential swelling on the charge density, the influence of a mixed electrolyte on the potential developed in the gel at the limit of low ionic strength and the effects of incomplete dissociation of the carboxylic functional groups were in agreement with the Donnan potentials independently measured by the twofold steady-state voltammetric approach.